Case Study and Comparison of High Voltage Power Transformer Dissolved Gas Analysis Assessed by Different Standards - Azis Prasojo, Rahman; Fauzan Sholehudin, Muhammad; Rafi Hanif, Muhammad; Nurhadi, Slamet; Joto, Ruwah (International Journal of Frontier Technology and Engineering, 2023)
A power transformer is a vital equipment in a power system. To prevent transformer failure, it is necessary to assess the transformer condition, one of which is through the DGA test. IEC 60599 and IEEE C57.104 become guidance for transformer assessment through the DGA test. DGA is a method of determining transformer conditions and fault diagnosis by assessing transformer oil data samples. H2, CO2, C2H4, C2H2, C2H6, CH4, CO, O2, and N2 are among the dissolved gases measured to monitor transformer conditions. To determine the faults, the IRM, RRM, and DTM are used. The fault detected on 8 transformer case studies showed T1, T2, T3, PD, D1, and D2. Maintenance recommendations for 8 power transformers evaluated were presented.